Urban farming: Production risks of vegetable farming in Pekanbaru City, Riau Province, Indonesia - Vaulina Sisca; Elinur; Dewi Ilma Satriana; Maharani Tati (BIO Web of Conferences)
Urban agriculture provides an effective solution to meet the needs of urban residents while reducing dependency on external sources. This study aims to analyze (1) the characteristics of spinach and water spinach farmers, (2) vegetable cultivation technology, (3) sources of production risks, and (4) the level of production risks. The research was conducted in the Marpoyan Damai sub-district of Pekanbaru, with a sample size of 30 farmers. The results indicate that most farmers are between 43-49 years old, with most having elementary school education and 11-20 years of farming experience. The study also identified several sources of production risks, including extreme weather, diseases and pests, climate change, limited water supply, and technological advancements. Furthermore, the level of production risk was found to be moderate, with spinach showing higher variability in yield compared to water spinach. This research provides insights into the challenges urban vegetable farmers face in Pekanbaru.